Responsible Research Assessment: OPERAS activities and initiatives - Mystakopoulos, Fotis (Industrias Culturais (Universidade de Coimbra), 2024)
Initiated by the San Francisco Declaration on Research Assessment (DORA) in 2012, the movement for research assessment reform has been steadily advancing for over a decade. This push has been characterised by a series of initiatives, each building on the last, to reshape how research is evaluated. The Coalition for Advancing Research Assessment (CoARA) represents the latest effort, culminating in the creation of the Agreement on Reforming Research Assessment (ARRA). This agreement marks a si...